Tourist intensity in medium and small Spanish cities. Urban tourism research using a quantitative indicator: Tourism Intensity Index (TII) - Carmen Hidalgo Giralt; Antonio Palacios García; Diego Barrado Timón; Francisca Cea D’Ancona (Investigaciones Turísticas, 2023)
Urban tourism has experienced significant growth in recent decades, generating situations of overtourism and tourismophobia. In Spain, cities such as Barcelona, Sevilla, Valencia, and Madrid face the effects of excess tourism on a daily basis, even in times of the pandemic. The objective of this study is to determine whether an increase in tourism intensity has also occurred in small and medium-sized Spanish cities and, if so, to develop an assessment of the phenomenon. To this end, a Tourism Intensity Index (TII) has been designed and applied to international tourist flows and statistically tested (through cluster analysis and Student’s ‘t’ test), permitting not only a confirmation of the phenomenon but its characterization during the period 2003-2020 and its interpretation from a geographical perspective. This research shows that tourist intensity is a phenomenon that extends also to medium and small Spanish cities.